The age of deception nuclear diplomacy in treacherous times - El Baradei, Mohamed (Doha, Qatar Bloomsbury Qutar Foundation Publishing, 2011)
For the first time, the director of the UN's International Atomic Energy Agency and "man in the middle" of the planet's most explosive confrontations speaks out--on his dealings with America, negotiations with Iran, reform and democracy in the Middle East, and the prospects for a future free of nuclear weapons
Iraq, 1991-1998: unmasking a hidden program -- North Korea, 1992-2002: the case of the missing plutonium -- Iraq, 2002 and after: a needless war -- North Korea, 2003 and after: the nuclear weapons club adds a member -- Iran, 2003-2005: the riddle of Taqqiya -- Libya: discovery and dismantlement -- The nuclear bazaar of A. Q. Khan -- From Vienna to Oslo -- Iran, 2006: "not one centrifuge" -- Double standards -- Iran, 2007-2008: squandered opportunities -- Iran, 2009: in pursuit of a breakthrough -- Conclusion : the quest for human security
Includes bibliographical references and index
12 20
Keywords: Nuclear arms control -- Verification; Nuclear arms control; Nuclear nonproliferation